Potential Application of Porous Membrane from Blends of Homopolymer for Industrial Water Treatment - Akoumeh, Rayane; Elzein, Tamara; Rodriguez-Hernandez, Juan; Hassan, Mohammad K. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
The self-organization of matter has been extensively explored in recent years, and significant advancements have been made in the field of porous ordered films produced by the auto-assembly of different polymer materials, being block of copolymers, blends of homopolymers or amphiphilic polymers. The hierarchical ordering in micro-organized films, known also as Honeycomb (HC) structure, generates a significant increase of specifics characteristics enhancing certain properties of the materials. The preparation of self-assembled porous membrane is done by different approaches. We use hereby the bottom-up microporous structuring method specifically the breath figure (BF) approach to prepare highly-organized membrane from polymer blends. The foremost motives for using the BF are the simplicity of implementation and the adaptability to multiple systems which make it a robust and inexpensive technique for the production of structured surfaces. The honeycomb (HC) structures formed by the BF is a potential candidate for water treatment as a filtration membrane to treat stable oil-water emulsions encountered in the oil and gas industry. The use of homopolymer blends improves the selectivity, permeability and anti-fouling properties comparing to the commercial homopolymer membrane. This presentation will highlight the preparation of self-assembled blends of homopolymers membrane by BF and their performance for cleaning of industrial wastewater and the fouling/re-use potential.